Step 2 define the gestures k tbcd 2 tbcl velar glo

Info icon This preview shows pages 17–24. Sign up to view the full content.

Step #2: Define the gestures /k/ TBCD: -2 TBCL: velar GLO: spread / ɪ / TBCD: 6 TBCL: palatal GLO: close together /k/ TBCD: -2 TBCL: velar GLO: spread Step #3: Movements TTCD TTCL TBCD TBCL VEL Tongue Height for / ɪ /?
Image of page 17

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

Dynamical Systems for Speech Synthesis Dynamical System Equation for / ɪ / tongue height Goal? 6 Starting Point? -2 k = -1/2 Equation? Δx/Δt = -0.5x+3 For loop?
Image of page 18
Dynamical Systems for Speech Synthesis Dynamical System Equation for / ɪ / tongue height for 5 time steps Δx/Δt = -.5x + 3 x(1) = -2 n = 2 x(n) = x(n-1) + ((-.5 * x(n-1)) + 3) n = 3 x(n) = x(n-1) + ((-.5 * x(n-1)) + 3) x(1) = -2 for n = [2:6] x(n) = x(n-1) + ((-.5 * x(n-1)) + 3) end Ends at 5.75 Tongue height for word final /k/?
Image of page 19

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

Dynamical Systems for Speech Synthesis Dynamical System Equation for final / k / tongue height Goal? -2 Starting Point? 5.75 k = -1/2 Equation? Δx/Δt = -0.5x -1 For loop?
Image of page 20
Dynamical Systems for Speech Synthesis Dynamical System Equation for / k / tongue height for 5 time steps Δx/Δt =
Image of page 21

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

Dynamical Systems for Speech Synthesis /ɪ/ x(1) = -2 for n = [2:6] x(n) = x(n-1) + ((-.5 * x(n-1)) + 3) end /k/ for n = [7:11] x(n) = x(n-1) + ((-.5 * x(n-1)) - 1) end Time Positio n Initial -2 1 2 2 4 3 5 4 5.5 5 5.75 6 1.87 7 -.06 8 -1.03 9 -1.51 10 -1.76 0.0 1.0 2.0 3.0 4.0 5.0 6.0 7.0 8.0 9.0 10.0 -3 -2 -1 0 1 2 3 4 5 6 7 Tongue Body Height: TBCD Add the initial /k/?
Image of page 22
Dynamical Systems for Speech Synthesis x(1) = 1 /k/ for n =[2:6] x(n) = x(n-1) + ((-.5 * x(n-1)) + 1) end /ɪ/ for n = [7:11] x(n) = x(n-1) + ((-.5 * x(n-1)) + 3) end /k/ for n =[12:16] x(n) = x(n-1) + ((-.5 * x(n-1)) + 1) end
Image of page 23

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

For Loops For-loop for variable = [vector] equation end Dynamical Systems Equation x(1) = initial position for a = [# of frames] x(a) = x(a-1) + ((k * x(a-1)) + c) end
Image of page 24
This is the end of the preview. Sign up to access the rest of the document.
  • Spring '14
  • Dynamical systems, Dynamical systems theory, Dynamical System Equation

{[ snackBarMessage ]}

What students are saying

  • Left Quote Icon

    As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

    Student Picture

    Kiran Temple University Fox School of Business ‘17, Course Hero Intern

  • Left Quote Icon

    I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

    Student Picture

    Dana University of Pennsylvania ‘17, Course Hero Intern

  • Left Quote Icon

    The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

    Student Picture

    Jill Tulane University ‘16, Course Hero Intern